KRAS, GNAS, and RNF43 mutations in intraductal papillary mucinous neoplasm of the pancreas: a meta-analysis - Lee, Ju-Han (Springerplus, 2016)
BACKGROUND: The prevalence and clinical significances of KRAS, GNAS, and RNF43 mutations in patients with pancreatic intraductal papillary mucinous neoplasm (IPMN) remain elusive. To evaluate the incidence of the gene mutations and clinicopathologic differences between KRAS and GNAS mutations in pancreatic cystic lesions, we performed a meta-analysis of published 33 KRAS, 11 GNAS, and 4 RNF43 studies including 1253, 835, and 143 cases, respectively. METHODS: We pooled the results of relevant studies identified using the PubMed and EMBASE databases. The effect sizes of outcome parameters were computed by the prevalence rate, weighted mean difference, or odds ratio (OR) using a random-effects model. RESULTS: The pooled prevalence of KRAS, GNAS, and RNF43 mutations in IPMN was 61, 56, and 23 %, respectively. The KRAS (OR 7.4 and 71.2) and GNAS (OR 30.2 and 15.3) mutations were more frequently found in IPMNs than in mucinous cystic neoplasms and in serous cystadenomas, respectively. Of the microscopic subtypes of IPMN, KRAS and GNAS were frequently mutated in gastric type (OR 2.7, P < 0.001) and intestinal type (OR 3.0, P < 0.001), respectively. KRAS mutation was infrequently found in high-grade dysplasia lesions of IPMN (OR 0.6, P = 0.032). GNAS mutation was associated with male (OR 1.9, P = 0.012). CONCLUSIONS: This meta-analysis supports that KRAS and GNAS mutations could be diagnostic markers for IPMN. In addition, the frequencies of KRAS and GNAS mutations in IPMNs are highly variable according to the microscopic duct subtypes, reflecting their independent roles in the IPMN-adenocarcinoma sequence. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2847-4) contains supplementary material, which is available to authorized users.